The Historical Background of the King James Bible - Gasparyan, Seda (Armenian Folia Anglistika, 2020)
The present article aims to investigate the historical and religious circumstances which incited King James to initiate and start the translation of the Holy Script anew though two other versions of the Bible in English were already there. The stormy period England and the English Church were going through in mid-XVI century and the succession of Prince James VI of Scotland to throne (who became King James I of England) and his unfavorable attitude towards Protestantism made him conceive the idea of the necessity of creating a new English version of the Bible which will provide appropriate influence on the Church and keep it away from Calvinist views and ideas. Through the employment of the descriptive method, the author on the other hand tries to analyse the most prominent events and activities which preconditioned the creation of the new English version of the Bible, known as the King James Bible, which has long proved to be the best translation of the Bible in English.